Evaluation of the breeding practices and population trend of the Fogera cattle breed in Ethiopia - Tesfa, Assemu; Bimerew, Tewodross; Tilahune, Mekonnen; Kassahun, Demelash; Kebede, Adebabaye; Mengesha, Wondimagegn (Frontiers in Animal Science, 2022)
The study was conducted to estimate the population size, herd structure, and breeding objectives of Fogera cattle in Ethiopia. The study was conducted in purposively selected 23 kebeles of five districts of three zones bordering Lake Tana. Interviewed farmers were selected based on their livestock ownership. Primary information on the general production system and trend of Fogera cattle was collected from 527 farmers and a population count was done from 479 respondents. For identification of pure Fogera cattle from the mixed and highland zebu breeds, colored photographs of the three breeds were used by each enumerator. Kebele administrators and elders, district and zone officials were assisting the operation to identify the true type of Fogera cattle. MS-Excel (2010) and SPSS (version 20) were used to analyse the population size and the production system, respectively. The overall cattle holding per household was 7.03±0.2 heads. From the analysis of multiple responses, the dominant reasons for keeping cattle in the herd were traction power (96.67%), milk (92.76%), and manure (83.95%). Respondents of 64.65% practice culling both male and female animals from their herd. Interviewed farmers select bulls for mating by coat color (56.84%), body conformation (55.08%), and body size (47.46%). They also indicated that they select Fogera breed (48.63%), highland zebu (18.16%), and mixed (17.38%) as a bull for mating of their cattle. Based on the respondents' information, the trend of the Fogera breed gets decreasing (40%), increasing (13%), is stable (6%), and is not known (41%). From the total population estimated, households own relatively pure Fogera (41%), Fogera-Zebu mix (35%), and highland zebu (24%). In this study, the total estimated number of breeding Fogera cattle was 55, 646±1, 657 heads. From the study, it was concluded that the breed is declined and fit for genetic deterioration as the population size decreases due to shift of production lands to crop production, further lowers the productivity. As population estimation was done by morphological features, further research works supported by the molecular study should be conducted.